Numerical Modeling of the Fluid Flow in Continuous Casting Tundish with Different Control Devices - Zhu He; Kun Zhou; Shuang Liu; Wei Xiong; Baokuan Li (Abstract and Applied Analysis)
Numerical simulations were conducted to study the melt flow under the influence of control devices in a T-type two-strand bloom caster tundish via the open source Computational Fluid Dynamics software OpenFOAM. Three different cases were studied: a bare tundish, a tundish with two pairs of baffles, and a tundish equipped with a turbulence inhibitor and a pair of baffles. Turbulence inhibitor and baffles arrangement showed an improvement of the fluid flow characteristics, yielding lower values of dead volume and higher values of plug flow. With a turbulence inhibitor, the velocity of metal which flows directly toward the tundish floor is smaller and the turbulence kinetic energy of the melt top surface is lower than the other two arrangements.